2017
DOI: 10.1103/physrevb.95.245429
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Mössbauer effect to the study of subnanometer harmonic displacements in thin solids

Abstract: We measure subnanometer displacements of thin samples vibrated by piezotransducer. Samples contain 57 Fe nuclei, which are exposed to 14.4 keV γ-radiation. Vibration produces sidebands from a single absorption line of the sample. The sideband intensities depend on the vibration amplitude and its distribution along the sample. We developed a model of this distribution, which adequately describes the spectra of powder and stainless steel (SS) absorbers. We propose to filter γ-radiation through a small round hole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 41 publications
2
23
0
4
Order By: Relevance
“…In this paper we present the results of our new experiments with sodium ferrocyanide K 4 Fe(CN) 6 ·3H 2 O. In the previous report [14] we worked with the pressed powder of this salt. In the experiments, which we report here, powder crystals of sodium ferrocyanide were grind up and stirred in epoxy resin without hardener.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In this paper we present the results of our new experiments with sodium ferrocyanide K 4 Fe(CN) 6 ·3H 2 O. In the previous report [14] we worked with the pressed powder of this salt. In the experiments, which we report here, powder crystals of sodium ferrocyanide were grind up and stirred in epoxy resin without hardener.…”
mentioning
confidence: 95%
“…Vibrations of SS foil were studied in Refs. [14,15]. There, it was shown that SS foil vibrates as a whole (piston like).…”
mentioning
confidence: 99%
“…A different method of pulse compression was recently reported in [15][16][17][18]. The capabilities of this method was experimentally demonstrated for gamma photons with long duration of a single-photon wave packet [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The method [15,16] is also based on frequency modulation of the radiation field. However, in spite of subsequent phasing of the produced spectral components, absorption (removal) of a particular spectral component is used [15][16][17]. This removal method has many in common with other methods used before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation